Evaluation of three alternatives cost-effective culture media for Mycobacterium tuberculosis detection and drug susceptibility determination using the microscopic observation drug susceptibility (MODS) assay - Rodriguez, Jhojailith (2022)
Tuberculosis phenotypic detection assays are commonly used in low-resource countries. Therefore, reliable detection methods are crucial for early diagnosis and treatment. The microscopic observation drug susceptibility (MODS) assay is a culture-based test to detect Mycobacterium tuberculosis and characterize drug resistance in 7–10 days directly from sputum. The use of MODS is limited by the availability of supplies necessary for preparing the enriched culture. In this study, we evaluated three dry culture media that are easier to produce and cheaper than the standard one used in MODS [1]: an unsterilized powder-based mixed (Boldú et al., 2007) [2], a sterile-lyophilized medium, and (Sengstake et al., 2017) [3] an irradiated powder-based mixed. Mycobacterial growth and drug susceptibility were evaluated for rifampin, isoniazid, and pyrazinamide (PZA). The alternative cultures were evaluated using 282 sputum samples with positive acid-fast smears. No significant differences were observed in the positivity test rates. The positivity time showed high correlations (Rho) of 0.925, 0.889, and 0.866 between each of the three alternative media and the standard. Susceptibility testing for MDR and PZA showed an excellent concordance of 1 compared to the reference test. These results demonstrate that dry culture media are appropriate and advantageous for use in MODS in low-resource settings.